Education for Sustainable (ESD): Development of Android Media to Improve Students’ Chemical Literacy - Fazita Apritama Dewi Fau; Agneslina Esterlina Purba; Anita; Fajar Naqsyahbandi; Jajang Muhariyansah; Khilda Hasni Ijjati; Nurfahraini; Umi Arifatun; Zahrotul Ma waroh Ma waroh (Postgraduate, University of Mataram, 2025)
This research aims to develop mobile learning media based on Android media in education for sustainable (ESD) context to improve students’ chemical literacy on colloidal system subjects. Scientific issues are presented in each learning activity using this Android-based ESD learning media. The method used in this study was research and development with 4D model development (define, design, development, and disseminate). Media feasibility criteria for Android-based learning media products with ESD contexts on colloidal system materials are based on assessments by material experts, media experts, practicality tests by five teachers, and legibility tests by students. The results of the practicality test of android media by reviewers and peer reviewers showed a very good result and the readability test by students showed a mean score in the very good categoryThe findings confirm that Android-based ESD learning media is practical and effective for teaching colloidal systems in chemistry. The independent sample t-test showed a significant difference in chemical literacy between the control and experimental groups (p = 0.000 < 0.05), with an effect size of 2.194, classified as strong. This application enhances students' competencies in sustainable development by fostering awareness of limited natural resources, differentiating sustainable and unsustainable behaviors, and improving ESD-based numerical literacy. Overall, the study validates the feasibility of this media in enhancing students' chemical literacy.